Novel waterproof phase-change thermal insulation mortar and preparation method thereof
The diatomaceous earth is treated by calcining, pickling and hydrophobic modification, and the preparation of fixed phase change materials and polysorbate in combination with vacuum impregnation method, which solves the cracking problem of hydraulic large-volume concrete structure when temperature changes, and improves the phase change insulation mortar The waterproof and thermal insulation properties extend the service life.
Patent Information
- Application Number
- CN202411302998.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-10
AI Technical Summary
The existing hydraulic large volume concrete structures are prone to cracks when temperature changes, and the existing phase change insulation mortar process is complex, has high cost, poor insulation performance, high water absorption rate, affects service life.
Calcination, pickling and hydrophobic modification are used to treat diatomaceous earth, and morphological phase change materials are prepared by vacuum impregnation. Combined with polysorbate, an efficient hydrophobic barrier is formed to improve the hydrophobicity and insulation properties of the mortar.
It significantly improves the mortar's impermeability, freezing resistance and waterproof performance, extends its service life, and enhances the thermal insulation performance and overall stability.
Smart Images

Figure CN119285291A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mortar building materials, in particular to a novel waterproof phase-change thermal insulation mortar and a preparation method thereof. Background Art
[0002] During the construction and operation of large-volume concrete structures of hydraulic structures, tensile stress is often generated inside the structure due to temperature changes. Once the tensile stress exceeds the allowable range of the design, it is easy to cause cracks. Temperature cracks will destroy the integrity and impermeability of the structure, resulting in a decrease in the durability of the concrete and endangering operational safety. Insulation treatment on the concrete surface is an important means to reduce the temperature difference between the inside and outside and achieve temperature control and crack prevention of large-volume concrete of hydraulic structures. In related technologies, the commonly used insulation materials for large-volume hydraulic structures are mainly organic insulation materials and inorganic insulation materials. Among them, organic thermal insulation materials, such as polystyrene foam, polyvinyl chloride foam, phenolic foam and expanded polyurethane foam, are light and have excellent thermal insulation performance, but at the same time, organic thermal insulation materials have poor adhesion to inorganic cement-based structures, are prone to forming cold and hot bridges, are prone to aging and brittleness, and are prone to falling off during use. Quality accidents; inorganic thermal insulation materials, such as rock wool, glass wool, expanded perlite and inorganic fiber spray insulation materials, have stable performance, good durability, high bonding strength with the substrate, and good thermal insulation performance. They are the main choice for building structure insulation systems, but they have high hygroscopicity and their thermal insulation performance is significantly reduced after being damp. If used for hydraulic construction insulation, it is often seriously affected by its moisture absorption and dampness. Therefore, studying a new type of inorganic thermal insulation material that fits the hydraulic field is of great significance to achieving temperature control, crack prevention and life extension of large-volume hydraulic buildings.
[0003] Among inorganic thermal insulation materials, phase change thermal insulation mortar is a dry-mixed mortar composed of cement, lightweight aggregate loaded with phase change materials and coated or phase change microcapsules and admixtures. It is a new type of thermal insulation material with heat storage, temperature regulation and energy saving. It has a high bonding strength with the substrate, simple construction operation, environmental protection, and high durability, and has broad application prospects. However, due to process and technical problems, most of the phase change thermal insulation mortars on the market are in the form of microcapsule packaging, which has a complex process and high cost. Phase change lightweight aggregate has the problems of low phase change material loading rate, general thermal insulation performance and poor thermal stability. Like other inorganic mortar materials, it also has the problem of high water absorption. The migration and retention of water in the thermal insulation system will have a serious impact on the performance and service life of the thermal insulation mortar. Based on the above statements, the present application provides a new waterproof phase change thermal insulation mortar and a preparation method thereof. Summary of the invention
[0004] The present invention provides a novel waterproof phase-change thermal insulation mortar and a preparation method thereof, aiming to solve at least one technical problem existing in the prior art mentioned in the background technology.
[0005] The present invention provides the following technical solutions to achieve the above objectives:
[0006] A novel waterproof phase-change thermal insulation mortar, comprising the following raw materials in weight ratio: 500 parts of silicate cement, 150 parts of water, 250-450 parts of fine sand, 50-200 parts of shaped phase-change material, and 5-15 parts of polycarboxylate water reducer
[0007] And 1-5 parts of polysorbate.
[0008] Furthermore, the raw materials include: 500 parts of silicate cement, 150 parts of water, 350 parts of fine sand, 150 parts of shaped phase change material, 10 parts of polycarboxylate water reducer and 3 parts of polysorbate.
[0009] Furthermore, the following steps are included:
[0010] S1, calcining diatomaceous earth to obtain calcined diatomaceous earth;
[0011] S2, acid leaching the calcined diatomite to obtain acid-washed diatomite;
[0012] S3, hydrophobically modifying the acid-washed diatomite to obtain hydrophobically modified diatomite;
[0013] S4, adding n-hexadecane to the hydrophobically modified diatomaceous earth, and obtaining a shape-fixed phase change material by a vacuum impregnation method;
[0014] S5, weighing the shape-fixed phase change material, polycarboxylate water-reducing agent and polysorbate respectively by weight, adding them into water and stirring evenly to obtain premix A;
[0015] S6. Weigh silicate cement and fine sand by weight, mix and stir evenly to obtain premix B;
[0016] S7, mixing premix A and premix B to obtain a finished product.
[0017] Furthermore, in S1, diatomaceous earth is calcined at 450° C. for 4 hours and then cooled to room temperature to obtain calcined diatomaceous earth.
[0018] Furthermore, S2 includes placing the calcined diatomite in a 20wt% sulfuric acid solution, acid-leaching it in a constant temperature water bath at 80°C for 2 hours, filtering it, washing the filter residue with distilled water until the pH reaches 7, and drying and grinding the filter residue to obtain acid-washed diatomite.
[0019] Furthermore, the S3 comprises the following steps:
[0020] S301, mixing the acid-washed diatomaceous earth and the ethanol aqueous solution, and adding glacial acetic acid solution to adjust the pH of the mixed solution to 4;
[0021] S302, pre-stirring for 30 minutes under heating conditions at 70°C, adding a silane coupling agent and stirring for 2 hours, and filtering and washing to obtain hydrophobically modified diatomaceous earth.
[0022] Furthermore, in S301, the ratio of the acid-washed diatomaceous earth to the ethanol aqueous solution is 25 g of the acid-washed diatomaceous earth to 220 mL of the ethanol aqueous solution; the volume ratio of ethanol to water in the ethanol aqueous solution is 1:1.
[0023] Furthermore, the amount of silane coupling agent added in S302 is 3.75 g of silane coupling agent for 25 g of acid-washed diatomaceous earth.
[0024] Furthermore, the S4 comprises the following steps:
[0025] S401, taking hydrophobically modified diatomaceous earth and subjecting it to vacuum treatment;
[0026] S402, taking n-hexadecane with a quantity of 4 times the amount of the hydrophobically modified diatomaceous earth and mixing it with the hydrophobically modified diatomaceous earth, and adjusting the pressure to 65 kPa and continuing the vacuum treatment for 90 minutes, and then adding air to adjust the pressure to standard atmospheric pressure to obtain a mixture of n-hexadecane and the hydrophobically modified diatomaceous earth;
[0027] S403, repeatedly hot filtering the mixture of n-hexadecane and hydrophobically modified diatomaceous earth until a granular sample appears;
[0028] S404, vacuum drying the granular sample at 80°C for 24 hours to obtain a shaped phase change material.
[0029] Furthermore, the silane coupling agent is KH-570.
[0030] Beneficial Effects
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention adopts a three-step method of calcination, acid washing and hydrophobic modification to treat diatomite. On the basis of reducing impurities and increasing pore volume, the diatomite is modified from its own hydrophilicity to hydrophobicity and lipophilicity, further enhancing the adsorption capacity of diatomite to n-hexadecane, which can significantly increase the thermal enthalpy and volume stability of the shape-fixed phase change material.
[0033] 2. The present invention adopts a vacuum impregnation method to prepare a shaped phase change material. After the vacuum impregnation is completed, hot filtration is repeatedly performed, the granular sample on the filter paper is collected, and vacuum drying is continued. A micro-rough structure can be formed on the surface of the shaped phase change material, which further enhances the hydrophobicity of the shaped phase change material and improves the overall hydrophobicity of the phase change thermal insulation mortar.
[0034] 3. The present invention adopts the addition of polysorbate and improves the construction process, which can improve the working performance of the mortar, and at the same time make the dispersion of the shaped phase change material in the mortar more uniform, thereby forming an effective hydrophobic barrier inside the mortar, so that the phase change thermal insulation mortar achieves overall hydrophobicity.
[0035] 4. The present invention significantly improves the mortar's impermeability, frost resistance and waterproof performance by adding shaped phase change materials. It has good durability, corrosion resistance and longer service life, and has very broad application prospects in the field of hydraulic construction materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below only relate to some embodiments of the present invention, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative labor.
[0037] Figure 1 This is a scanning electron microscope photograph of the shaped phase change material of the present invention at a magnification of 5.00kx;
[0038] Figure 2 This is a contact angle test result diagram of the waterproof phase-change thermal insulation mortar of Example 1 of the present invention;
[0039] Figure 3 This is a contact angle test result diagram of the waterproof phase-change thermal insulation mortar of Example 2 of the present invention;
[0040] Figure 4 This is a contact angle test result diagram of the waterproof phase-change thermal insulation mortar of Example 3 of the present invention;
[0041] Figure 5 This is a contact angle test result diagram of the waterproof phase-change thermal insulation mortar of Example 4 of the present invention;
[0042] Figure 6 This is a physical picture of the waterproof phase-change thermal insulation mortar of Example 5 of the present invention; DETAILED DESCRIPTION
[0043] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0044] Example 1. A novel waterproof phase-change thermal insulation mortar is made from the following raw materials by weight: 500 kg of silicate cement, 150 kg of water, 350 kg of fine sand, 150 kg of shaped phase-change material, 10 kg of polycarboxylate water reducer, and 3 kg of polysorbate;
[0045] Among them, the silicate cement is ordinary silicate cement PO42.5, purchased from Hubei Huaxin Cement Co., Ltd.; the fine sand is 100-200 mesh quartz sand, purchased from Changsha Hongshun Mining Technology Co., Ltd.; the purity of diatomaceous earth is CP, purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd.; the purity of n-hexadecane is AR, purchased from Wuhan Xinshenshi Chemical Technology Co., Ltd.; the polycarboxylate water reducer is A series of polycarboxylic acid high-performance water-reducing agents were purchased from Jiangsu Subote New Materials Co., Ltd.; polysorbate with a purity of CP was purchased from Wuhan Xinshenshi Chemical Technology Co., Ltd.; water was tap water that met the requirements of "JGJ 63-2006 Concrete Water Standard".
[0046] The steps of making the new waterproof phase change thermal insulation mortar from the above raw materials are as follows:
[0047] S1, calcining diatomite in a muffle furnace at 450° C. for 4 hours, and cooling to room temperature to obtain calcined diatomite; wherein organic impurities and carbonate compounds in the diatomite are removed by calcination;
[0048] S2, placing the calcined diatomite in a 20wt% sulfuric acid solution, acid-leaching in a constant temperature water bath at 80°C for 2 hours, filtering, washing the filter residue with distilled water until the pH reaches 7, and drying and grinding the filter residue to obtain acid-washed diatomite; wherein the acid washing of the calcined diatomite is to remove impurities in the calcined diatomite and increase the pore volume of the calcined diatomite;
[0049] S3: S301, according to the ratio of 25g acid-washed diatomaceous earth: 220mL ethanol aqueous solution, weigh 25kg acid-washed diatomaceous earth, add it into 220L ethanol and water in a volume ratio of 1:1 ethanol aqueous solution, and add glacial acetic acid solution to adjust the pH of the mixed solution to 4; S302, after pre-stirring for 30min under heating conditions at 70℃, add silane coupling agent KH-570, stir at high speed for 2 hours, filter and wash to obtain hydrophobically modified diatomaceous earth; wherein, the pH value must be strictly adjusted to 4, if the pH value is greater than or less than 4, the hydrophobic modification effect will be reduced; the amount of silane coupling agent added is 3.75g silane coupling agent for 25g acid-washed diatomaceous earth; the acid-washed diatomaceous earth is modified from its own hydrophilicity to hydrophobicity and lipophilicity, further enhancing the adsorption amount of diatomaceous earth to n-hexadecane, and increasing the thermal enthalpy and volume stability of the fixed phase change material;
[0050] S4: S401, weigh 20kg of hydrophobically modified diatomaceous earth and put it into a suction filtration bottle, connect it to a circulating water vacuum pump device, and exhaust the air in the pores of the diatomaceous earth. This process lasts for 20 minutes; S402, weigh 80kg of liquid n-hexadecane and mix it with the hydrophobically modified diatomaceous earth, and adjust the pressure to 65kPa to continue vacuum treatment for 90 minutes, then add air to adjust to standard atmospheric pressure; pour the weighed 80kg of liquid n-hexadecane into the suction filtration bottle to cover the hydrophobically modified diatomaceous earth sample, and continue vacuum treatment for 90 minutes at a vacuum pressure of 65kPa; S403, The mixture is repeatedly hot filtered until a granular sample appears; S404, the granular sample is vacuum dried at 80°C for 24 hours to obtain a fixed-shape phase change material; wherein, the vacuum treatment for 90 minutes is the shortest time for the hydrophobically modified diatomaceous earth to fully absorb the liquid n-hexadecane, and the absorption amount will not increase if it is more than 90 minutes, while the absorption is insufficient if it is less than 90 minutes. The use of a suction filtration bottle can facilitate the vacuum treatment of the hydrophobically modified diatomaceous earth and the addition of liquid n-hexadecane; by vacuum drying the granular sample at 80°C for 24 hours, a micro-rough structure can be formed on the surface of the fixed-shape phase change material, thereby further enhancing the hydrophobicity of the fixed-shape phase change material;
[0051] S5, weighing the corresponding shape-fixed phase change material, polycarboxylate water-reducing agent and polysorbate respectively by weight, adding them into water and stirring evenly to obtain premix A;
[0052] S6. Weigh cement and fine sand by weight, mix and stir evenly to obtain premix B;
[0053] S7, mixing premix A and premix B to obtain a finished product.
[0054] Example 2. The preparation method steps of this example are similar to those of Example 1, except that: 500 kg of ordinary Portland cement, 150 kg of water, 350 kg of fine sand, 150 kg of shaped phase change material, 10 kg of polycarboxylate water reducer, and 3 kg of polysorbate are weighed respectively.
[0055] The steps of making the new waterproof phase change thermal insulation mortar from the above raw materials are as follows:
[0056] S1, calcining diatomite in a muffle furnace at 450° C. for 4 hours, and cooling to room temperature to obtain calcined diatomite;
[0057] S2, placing the calcined diatomite in a 20wt% sulfuric acid solution, acid-leaching in a constant temperature water bath at 80°C for 2 hours, filtering, washing the filter residue with distilled water until the pH reaches 7, and drying and grinding the filter residue to obtain acid-washed diatomite;
[0058] S3: S301, weigh 20kg of hydrophobically modified diatomaceous earth and put it into a suction filtration bottle, connect it to a circulating water vacuum pump device, and exhaust the air in the pores of the diatomaceous earth. This process lasts for 20 minutes; S302, weigh 80kg of liquid n-hexadecane and mix it with the hydrophobically modified diatomaceous earth, and adjust the pressure to 65kPa to continue vacuum treatment for 90 minutes, then add air to adjust to standard atmospheric pressure; pour the weighed 80kg of liquid n-hexadecane into the suction filtration bottle to cover the hydrophobically modified diatomaceous earth sample, and continue vacuum treatment for 90 minutes at a vacuum pressure of 65kPa; S303, repeatedly heat filter the mixture of n-hexadecane and hydrophobically modified diatomaceous earth until a granular sample appears; S304, vacuum dry the granular sample at 80°C for 24 hours to obtain a shaped phase change material;
[0059] S5, weighing the corresponding shape-fixed phase change material and polycarboxylate water-reducing agent respectively by weight, adding them into water and stirring evenly to obtain premix A;
[0060] S6. Weigh cement and fine sand by weight, mix and stir evenly to obtain premix B;
[0061] S7, mixing premix A and premix B to obtain a finished product.
[0062] Example 3. The preparation method steps of this example are similar to those of Example 1, except that: 500 kg of ordinary Portland cement, 150 kg of water, 350 kg of fine sand, 150 kg of shaped phase change material, and 10 kg of polycarboxylate water reducer.
[0063] The steps of making the new waterproof phase change thermal insulation mortar from the above raw materials are as follows:
[0064] S1, calcining diatomite in a muffle furnace at 450° C. for 4 hours, and cooling to room temperature to obtain calcined diatomite;
[0065] S2, placing the calcined diatomite in a 20wt% sulfuric acid solution, acid-leaching in a constant temperature water bath at 80°C for 2 hours, filtering, washing the filter residue with distilled water until the pH reaches 7, and drying and grinding the filter residue to obtain acid-washed diatomite;
[0066] S3: According to the ratio of 25g acid-washed diatomaceous earth to 220mL ethanol aqueous solution, 25kg acid-washed diatomaceous earth was weighed and added into 220L ethanol and water aqueous solution with a volume ratio of 1:1, and glacial acetic acid solution was added dropwise to adjust the pH of the mixed solution to 4; S302, after pre-stirring for 30min under heating conditions at 70°C, silane coupling agent KH-570 was added, high-speed stirring was performed for 2 hours, and hydrophobically modified diatomaceous earth was obtained after filtration and washing;
[0067] S4: S401, weigh 20kg of hydrophobically modified diatomaceous earth and put it into a suction filtration bottle, connect it to a circulating water vacuum pump device, and exhaust the air in the pores of the diatomaceous earth. This process lasts for 20 minutes; S402, weigh 80kg of liquid n-hexadecane and mix it with the hydrophobically modified diatomaceous earth, and adjust the pressure to 65kPa to continue vacuum treatment for 90 minutes, then add air to adjust to standard atmospheric pressure; pour the weighed 80Kg of liquid n-hexadecane into the suction filtration bottle to cover the hydrophobically modified diatomaceous earth sample, and continue vacuum treatment at a vacuum pressure of 65kPa for 90 minutes;
[0068] S403, repeatedly hot-filtering the mixture of n-hexadecane and hydrophobically modified diatomaceous earth until a granular sample appears; S404, vacuum-drying the granular sample at 80° C. for 24 hours to obtain a shaped phase change material;
[0069] S5, weighing the corresponding shape-fixed phase change material and polycarboxylate water-reducing agent respectively by weight, adding them into water and stirring evenly to obtain premix A;
[0070] S6. Weigh cement and fine sand by weight, mix and stir evenly to obtain premix B;
[0071] S7, mixing premix A and premix B to obtain a finished product.
[0072] Example 4. The preparation method steps of this example are similar to those of Example 1, except that: 500 kg of ordinary Portland cement, 150 kg of water, 450 kg of fine sand, 50 kg of shaped phase change material, 5 kg of polycarboxylate water reducer, and 1 kg of polysorbate.
[0073] The steps of making the new waterproof phase change thermal insulation mortar from the above raw materials are as follows:
[0074] S1, calcining diatomite in a muffle furnace at 450° C. for 4 hours, and cooling to room temperature to obtain calcined diatomite;
[0075] S2, placing the calcined diatomite in a 20wt% sulfuric acid solution, acid-leaching in a constant temperature water bath at 80°C for 2 hours, filtering, washing the filter residue with distilled water until the pH reaches 7, and drying and grinding the filter residue to obtain acid-washed diatomite;
[0076] S3: S301, according to the ratio of 25g acid-washed diatomaceous earth: 220mL ethanol aqueous solution, weigh 25Kg acid-washed diatomaceous earth, add it to 220L ethanol and water in a volume ratio of 1:1 ethanol aqueous solution, and add glacial acetic acid solution dropwise to adjust the pH of the mixed solution to 4; S302, after pre-stirring for 30min under heating conditions at 70°C, add silane coupling agent KH-570, stir at high speed for 2 hours, and obtain hydrophobically modified diatomaceous earth after filtration and washing;
[0077] S4: S401, weigh 20 kg of hydrophobically modified diatomaceous earth and put it into a suction filtration bottle, connect it to a circulating water vacuum pump device, and exhaust the air in the pores of the diatomaceous earth. This process lasts for 20 minutes; S402, weigh 80 kg of liquid n-hexadecane and mix it with the hydrophobically modified diatomaceous earth, and adjust the pressure to 65 kPa to continue vacuum treatment for 90 minutes, then add air to adjust to standard atmospheric pressure; pour the weighed 80 kg of liquid n-hexadecane into the suction filtration bottle to cover the hydrophobically modified diatomaceous earth sample, and continue vacuum treatment at a vacuum pressure of 65 kPa for 90 minutes;
[0078] S403, repeatedly hot-filtering the mixture of n-hexadecane and hydrophobically modified diatomaceous earth until a granular sample appears; S404, vacuum-drying the granular sample at 80° C. for 24 hours to obtain a shaped phase change material;
[0079] S5, weighing the corresponding shape-fixed phase change material, polycarboxylate water-reducing agent and polysorbate respectively by weight, adding them into water and stirring evenly to obtain premix A;
[0080] S6. Weigh cement and fine sand by weight, mix and stir evenly to obtain premix B;
[0081] S7, mixing premix A and premix B to obtain a finished product.
[0082] Example 5. The preparation method steps of this example are the same as those of Example 1, except that: 500 kg of ordinary Portland cement, 150 kg of water, 350 kg of fine sand, 200 kg of shaped phase change material, 10 kg of polycarboxylate water reducer, and 3 kg of polysorbate.
[0083] The steps of making the new waterproof phase change thermal insulation mortar from the above raw materials are as follows:
[0084] S1, calcining diatomite in a muffle furnace at 450° C. for 4 hours, and cooling to room temperature to obtain calcined diatomite;
[0085] S2, placing the calcined diatomite in a 20wt% sulfuric acid solution, acid-leaching in a constant temperature water bath at 80°C for 2 hours, filtering, washing the filter residue with distilled water until the pH reaches 7, and drying and grinding the filter residue to obtain acid-washed diatomite;
[0086] S3: S301, according to the ratio of 25g acid-washed diatomaceous earth: 220mL ethanol aqueous solution, weigh 25kg acid-washed diatomaceous earth, add it to 220L ethanol and water in a volume ratio of 1:1 ethanol aqueous solution, and add glacial acetic acid solution dropwise to adjust the pH of the mixed solution to 4; S302, after pre-stirring for 30min under heating conditions at 70°C, add silane coupling agent KH-570, stir at high speed for 2 hours, filter and wash to obtain hydrophobically modified diatomaceous earth;
[0087] S4: S401, weigh 20 kg of hydrophobically modified diatomaceous earth and put it into a suction filtration bottle, connect it to a circulating water vacuum pump device, and exhaust the air in the pores of the diatomaceous earth. This process lasts for 20 minutes; S402, weigh 80 kg of liquid n-hexadecane and mix it with the hydrophobically modified diatomaceous earth, and adjust the pressure to 65 kPa to continue vacuum treatment for 90 minutes, then add air to adjust to standard atmospheric pressure; pour the weighed 80 kg of liquid n-hexadecane into the suction filtration bottle to cover the hydrophobically modified diatomaceous earth sample, and continue vacuum treatment at a vacuum pressure of 65 kPa for 90 minutes;
[0088] S403, repeatedly hot-filtering the mixture of n-hexadecane and hydrophobically modified diatomaceous earth until a granular sample appears; S404, vacuum-drying the granular sample at 80° C. for 24 hours to obtain a shaped phase change material;
[0089] S5, weighing the corresponding shape-fixed phase change material, polycarboxylate water-reducing agent and polysorbate respectively by weight, adding them into water and stirring evenly to obtain premix A;
[0090] S6. Weigh cement and fine sand by weight, mix and stir evenly to obtain premix B;
[0091] S7, mixing premix A and premix B to obtain a finished product.
[0092] Experimental example. According to the test standard, the phase change thermal insulation mortar prepared in Examples 1-5 of the present invention was poured into a test mold to prepare a test sample, covered with a plastic film, and cured for one day at a temperature of 25°C and a relative humidity of 95%, and then removed from the mold and cured for 28 days. After the curing was completed, the performance of the samples was tested.
[0093] The phase change thermal insulation mortar provided in the above-mentioned embodiments 1-4 was tested as follows:
[0094] Contact angle test: Using SDC-200S (Guangdong Dainte Intelligent Technology Co., Ltd.) instrument, 5 μL of water droplets were taken for each test.
[0095] According to the national standard GB / T 20473-2021 "Building Thermal Insulation Mortar", the compressive strength and softening coefficient of the specimens are tested, and the specimen specifications are 70.7mmx70.7mmx70.7mm.
[0096] According to the national standard GB / T 10294-2008 "Determination of steady-state thermal resistance and related properties of insulation materials - Guarded hot plate method", the thermal conductivity of the sample was tested using a TPMBE-3030 flat plate thermal conductivity meter, and the specimen size was 300mmx300mmx30mm.
[0097] The test results are shown in Table 1 below:
[0098] Table 1 Performance of phase change thermal insulation mortar in Example
[0099]
[0100] It can be seen from the data shown in Table 1 above that the waterproof and thermal insulation mortar prepared in Example 1 of the present application has excellent comprehensive performance, and has high waterproof, high thermal insulation and other properties.
[0101] It can be seen from the data shown in Examples 1 and 2 that the preparation method hydrophobically modifies diatomite, and the modified diatomite is used to prepare a shaped phase change material for thermal insulation mortar, which can significantly improve the waterproof, thermal insulation and mechanical properties of the mortar.
[0102] It can be seen from the data shown in Examples 1 and 3 that the addition of polysorbate during the preparation of the thermal insulation mortar in the present preparation method can make the shaped phase change material more evenly dispersed in the thermal insulation mortar, thereby further improving the comprehensive performance of the mortar.
[0103] It can be seen from the data shown in Example 1 and Example 4 that when preparing thermal insulation mortar using this preparation method, by adding more shaped phase change materials within a certain range, the waterproofness and thermal insulation properties of the sample can be significantly improved, and the mechanical properties are slightly reduced.
[0104] It can be seen from Examples 1 and 5 that when the present preparation method is used to prepare thermal insulation mortar, the working performance of the mortar is reduced due to the high dosage of the fixed-shape phase change material, and part of the fixed-shape phase change material is broken during the stirring process, resulting in a large amount of n-hexadecane leakage, which significantly affects the mechanical properties and thermal insulation effect of the mortar.
[0105] Obviously, the above is only a part of the embodiments of the present invention, not all of the embodiments. The above embodiments are not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and variations. Any combination, modification, equivalent replacement, improvement and all other embodiments that can be made by those of ordinary skill in the art within the spirit and principle of the present invention should be within the protection scope of the present invention.
Claims
1. A new waterproof phase-change thermal insulation mortar, characterized by: The invention comprises the following raw materials in weight proportion: 500 parts of silicate cement, 150 parts of water, 250-450 parts of fine sand, 50-200 parts of shaped phase change material, 5-15 parts of polycarboxylate water reducer and 1-5 parts of polysorbate.
2. The novel waterproof phase-change thermal insulation mortar according to claim 1 is characterized in that: The raw materials are 500 parts of silicate cement, 150 parts of water, 350 parts of fine sand, 150 parts of shaped phase change material, 10 parts of polycarboxylate water reducer and 3 parts of polysorbate.
3. The method for preparing the novel waterproof phase-change thermal insulation mortar according to claim 1 or 2, characterized in that: The following steps are involved: S1, calcining diatomaceous earth to obtain calcined diatomaceous earth; S2, acid leaching the calcined diatomite to obtain acid-washed diatomite; S3, hydrophobically modifying the acid-washed diatomite to obtain hydrophobically modified diatomite; S4, adding n-hexadecane to the hydrophobically modified diatomaceous earth, and obtaining a shape-fixed phase change material by a vacuum impregnation method; S5, weighing the shape-fixed phase change material, polycarboxylate water-reducing agent and polysorbate respectively by weight, adding them into water and stirring evenly to obtain premix A; S6. Weigh silicate cement and fine sand by weight, mix and stir evenly to obtain premix B; S7, mixing premix A and premix B to obtain a finished product.
4. The method for preparing the novel waterproof phase-change thermal insulation mortar according to claim 3 is characterized in that: In S1, diatomaceous earth is calcined at 450° C. for 4 hours and then cooled to room temperature to obtain calcined diatomaceous earth.
5. The method for preparing the novel waterproof phase-change thermal insulation mortar according to claim 3 is characterized in that: The S2 comprises placing the calcined diatomite in a 20wt% sulfuric acid solution, acid-leaching it in a constant temperature water bath at 80°C for 2 hours, filtering it, washing the filter residue with distilled water until the pH reaches 7, and drying and grinding the filter residue to obtain the acid-washed diatomite.
6. The method for preparing the novel waterproof phase-change thermal insulation mortar according to claim 3 is characterized in that: The S3 comprises the following steps: S301, mixing the acid-washed diatomaceous earth and the ethanol aqueous solution, and adding glacial acetic acid solution to adjust the pH of the mixture to 4; S302, pre-stirring for 30 minutes under heating conditions at 70°C, adding a silane coupling agent and stirring for 2 hours, and filtering and washing to obtain hydrophobically modified diatomaceous earth.
7. The method for preparing the novel waterproof phase-change thermal insulation mortar according to claim 6 is characterized in that: The ratio of the acid-washed diatomaceous earth to the ethanol aqueous solution in S301 is 25 g of the acid-washed diatomaceous earth to 220 mL of the ethanol aqueous solution; the volume ratio of ethanol to water in the ethanol aqueous solution is 1:
1.
8. The method for preparing the novel waterproof phase-change thermal insulation mortar according to claim 6 is characterized in that: The amount of silane coupling agent added in S302 is 3.75 g of silane coupling agent for 25 g of acid-washed diatomaceous earth.
9. The method for preparing the novel waterproof phase-change thermal insulation mortar according to claim 3 is characterized in that: The S4 comprises the following steps: S401, taking hydrophobically modified diatomaceous earth and subjecting it to vacuum treatment; S402, taking n-hexadecane with a quantity of 4 times the amount of the hydrophobically modified diatomaceous earth and mixing it with the hydrophobically modified diatomaceous earth, and adjusting the pressure to 65 kPa and continuing the vacuum treatment for 90 minutes, and then adding air to adjust the pressure to standard atmospheric pressure to obtain a mixture of n-hexadecane and the hydrophobically modified diatomaceous earth; S403, repeatedly hot filtering the mixture of n-hexadecane and hydrophobically modified diatomaceous earth until a granular sample appears; S404, vacuum drying the granular sample at 80°C for 24 hours to obtain a shaped phase change material.
10. The method for preparing the novel waterproof phase-change thermal insulation mortar according to claim 6, characterized in that: The silane coupling agent is KH-570.
Citation Information
Cited By
Thermal insulation and waterproof integrated phase change heat storage mortar and preparation method thereof
CN120483620A
Concrete internally-doped waterproof agent with multiple synergistic repair and anti-permeability functions as well as preparation method and application of concrete internally-doped waterproof agent
CN122102562A